In-depth analysis of scenarios and injuries in crashes between cyclists and commercial vehicles in Germany - Ron Schindler; Hanna Jeppsson (Traffic Safety Research, 2024)
Large vehicles such as buses and heavy goods vehicles (HGVs) pose a serious threat to cyclists and can cause serious injuries. Therefore, it is important to understand current safety issues related to these vehicles, to identify and to develop safety interventions that could address these issues. The aim of this study is to describe the characteristics of and injuries resulting from crashes between cyclists and buses and HGVs. In this study, the German In-Depth Accident Study (GIDAS) was queried for all cases that involved either a bus or a HGV and where the opponent was a cyclist. In total, 98 crashes with the involvement of both a bus and a cyclist, and 295 cases where both a HGV and a cyclist were involved, were identified for our analysis. The crashes with cyclists typically occur within city limits, during daylight conditions, on dry surfaces and with clear weather. The cyclists involved in these crashes are mainly male and cyclists under 18-years old account for 28% of crashes with buses, and 16% for crashes with HGVs. The most common crash scenarios are crossing scenarios and turning-off-a-road crashes. In bus crashes, the collision speeds are mainly below 35 km/h and injuries to lower extremities and head are dominating, caused by the road surface and the front of the bus. In HGV crashes, collision speeds are most often below 20 km/h and injuries to the head and thorax are most common, mainly caused by being run over.